Elucidating multisensory interactions in synaesthesia - Bargary, Gary (Trinity College (Dublin, Ireland). School of Psychology, 2008)
This work examines synaesthesia; a neurodevelopmental phenomenon widely believed to be the result of aberrant cross-talk from one cortical area to another. A number of behavioural measures were used to assess the nature of the aberrant crosstalk in synaesthesia. Also, 'normal' cross-talk between the senses was examined to gain insight into the mechanisms which enable cross-talk or multisensory interactions between the senses.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin